Kopi Arabika Kalosi Produk Unggulan Kabupaten Enrekang - Reta Reta; Dahlia Dahlia; Halimah Larekeng; Zulfitriani Dwiyanti Mustaka (Unri Conference Series: Community Engagement, 2019)
Arabica Coffee is one of the superior products of Enrekang Regency's plantation. SME Maqfirah as a coffee producer both in the form of green beans and roasted coffee products in Enrekang Regency faces the problem of not having production equipment so it needs supporting equipment to guarantee quality and increase the production. The aims for developing SME Maqfirah as the producer of kalosi arabica coffee by increasing production capacity, quality, and variety of products and emerging the market. The SME assistance program is implemented through the synergy between the Team of Politeknik Pertanian Negeri Pangkajene Kepulauan and the Enrekang Regency Industry Office in March-August 2018. The method of implementation is program socialization, counselling, assistance, and development in production and marketing. The implementation of science and technology resulting in the increase in production by 75%, increase in the quality of coffee flavour and aroma, increase in income, and the increase in marketing which has penetrated outside the province.